Design and Investigation of New Water-Soluble Forms of α-Tocopherol with Antioxidant and Antiglycation Activity Using Amphiphilic Copolymers of N-Vinylpyrrolidone - Yuliya V. Soldatova; Irina I. Faingold; Darya A. Poletaeva; Alexei V. Kozlov; Nina S. Emel'yanova; Igor I. Khodos; Dmitry A. Chernyaev; Svetlana V. Kurmaz (MDPI AG, 2023)
Water-soluble forms of α-tocopherol (TP) as an effective antioxidant were obtained by encapsulating it into nanoparticles (NPs) of amphiphilic copolymers of N-vinylpyrrolidone with triethylene glycol dimethacrylate (CPL1-TP) and N-vinylpyrrolidone with hexyl methacrylate and triethylene glycol dimethacrylate (CPL2-TP) synthesized by radical copolymerization in toluene. The hydrodynamic radii of NPs loaded with TP (3.7 wt% per copolymers) were typically ca. 50 or 80 nm depending on copolymer composition, media, and temperature. Characterization of NPs was accomplished by transmission electron microscopy (TEM), IR-, and 1H NMR spectroscopy. Quantum chemical modeling showed that TP molecules are capable to form hydrogen bonds with donor groups of the copolymer units. High antioxidant activity of both obtained forms of TP has been found by the thiobarbituric acid reactive species and chemiluminescence assays. CPL1-TP and CPL2-TP effectively inhibited the process of spontaneous lipid peroxidation as well as α-tocopherol itself. The IC50 values of luminol chemiluminescence inhibition were determined. Antiglycation activity against vesperlysine and pentosidine-like AGEs of TP water-soluble forms was shown. The developed NPs of TP are promising as materials with antioxidant and antiglycation activity and can be used in various biomedical applications.